Spark plasma sintered bioceramics – from transparent hydroxyapatite to graphene nanocomposites: a review. (17th February 2020) - Han, Young-Hwan; Gao, Ruoqi; Bajpai, Indu; Kim, Byung-Nam; Yoshida, Hidehiro; Nieto, Andy; Son, Hyoung-Won; Yun, Jondo; Jang, Byung-Koog; Jhung, Sungsil; Jingming, Zhao; Hwang, Kyu-Hong; et al.
ABSTRACT: Low toughness and wear resistance have limited application of many bioceramics in biomedical applications requiring load bearing capability. Spark plasma sintering (SPS) has widened the envelope of processing conditions available to produce bioceramics with new microstructural architectures. SPS has enabled realisation of transparent hydroxyapatite (HA) by providing the means to consolidate fully dense nanostructured HA. Recently, low-dimensional carbon nanomaterials, including carbon nanotubes (CNTs) and graphene/graphene nanoplatelets (GNP) have gained increasing attention as reinforcements due to their providing superior mechanical properties, favourable biocompatibility, and large specific surface area. Processing of these nanocomposites is done using SPS in order to consolidate the ceramics to full density in short time periods, while retaining the structure and properties of the nanomaterial reinforcements. This review focuses on recent progress on GNP/CNT reinforced HA and alumina nanocomposites, including mechanical properties, tribological behaviour, processing conditions, and mechanisms. Biocompatibility of these promising bioceramics with various cells/tissues are discussed.